The Social Psychology of Eating - Catellani, Patrizia; Carfora, Valentina (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
Our eating decisions are guided by several psychological dimensions: cognitive, emotional, value-based, social, and behavioural. The social psychology of eating helps us understand these dimensions and how we can promote healthy and sustainable eating to improve people's wellbeing. What is most important in deciding what we want to eat? What drives people to go vegan? Do we tend to eat more when we are nervous? Does it change our behavior when we sit at the table with others? Why do we put off starting the diet until the next week? How does online and offline communication influence our eating behaviour? Is it possible to help people change their eating habits thanks to artificial intelligence? These and other questions are answered in this book, with up-to-date literature references and pointers to the most promising developments in the field. An essential text for undergraduate and graduate students, as well as researchers in the fields of psychology and nutrition. Basic social psychology concepts to promote healthy and sustainable eating How food choices are guided by cognitive and emotional input Provides a systematic overview of communication strategies for changing eating behavior.
Chapter 1. Introduction -- Chapter 2. Food Choice -- Chapter 3. Cognitive Factors -- Chapter 4. Emotional Factors -- Chapter 5. Norms, Identities, and Values -- Chapter 6. Habits and Behaviour Change -- Chapter 7. Habits and Behaviour Change -- Chapter 8. Types of Messages -- Chapter 9. Characteristics of Recipients -- Chapter 10. Digital Communication and Artificial Intelligence.
Keywords: Psychology; Social psychology; Sociology; Nutrition; Food; Behavioral Sciences and Psychology; Social Psychology; Sociology of Food and Nutrition